Dairy manure compost pelleting process: A techno-economic analysis. (10th August 2021) - Alege, Femi Peter; Gu, Xiangyu; Tao, Haiying; Miito, Gilbert J.; Ndegwa, Pius M.
Abstract: Pelleting of dairy manure compost (C) with or without canola meal (CM) or fish meal (FM) is a promising value-addition process for enhanced and environmentally-friendly utilization of excess manure-nutrients, common in regional-centers with high concentrations of dairy production. Previous studies mostly focused on pellet production for bioenergy applications. However, this study looks at the techno-economic feasibility of the pelleting process from environmental and soil amendment standpoints. Consequently, this study investigated the potential profitability of pelleting dairy manure compost, as well as pertinent factors influencing the feasibility. The main components for the economic analysis modeling process included feedstock procurement, transportation and storage, pre-treatment and conditioning, pelleting, and post-pelleting operations including drying, sieving, and packaging. The cost-implications of different formulations of C, CM, and FM were also evaluated. Sensitivity analysis was conducted to assess the effects of the product recovery, interest rate, and the costs of feedstock, electricity, equipment, and personnel on the production of pelleted products. The minimum selling price (MSP) ranged from $77 ton −1 for the base product (pellets produced with 100% composts) to $150 ton −1 for products with 10% each of CM and FM. Based on the estimated base product selling price of $100 ton −1, the payback period, net present value, and discounted rate of return were 3.5 years, $2.2 million, and 38.2%, respectively. Sensitivity analysis indicated that the payroll-cost was the most important factor to MSP, followed by the feedstock cost and the product recovery, in that order. To improve the marketability of the product, optimization for bioenergy applications is recommended. Graphical abstract: Image 1 Highlights: The TEA was based on minimum selling price (MSP) and net present value (NPV). Breakeven potential is 3.5 years at MSP of $77 t −1 and 10-year NPV of $2.2 m. Profitability was most sensitive to equipment, feedstock, and personnel costs. Pelleting benefits the environment, soil, energy, and circular bioeconomy sectors.